Respuesta :

Try this option:

the function can be re-written in a form f(x)=(x+1)(x+1)(x-3);

The roots of the function are 3 and -1

Answer with explanation:

The given Polynomial function is:

 F(x)=  x³-x²-5 x -3

 By Rational root theorem , roots of the polynomial can be 1,-1, 3 ,-3.

F(3)=3³-3²-5×3-3

    =27-9-15-3

    = 0

So, 3 is one of the root of the equation.

That is, (x-3) will divide the whole polynomial.

F(x)=x³-x²-5 x -3

   =(x-3)(x²+2 x +1)

 = (x-3)(x+1)²

to get the roots.

1. x-3=0

⇒x=3

2.(x+1)²=0

⇒x+1=0

⇒x= -1

So, root of the polynomial function are=3, and ,-1.

Option B=3 and Option C= -1

Ver imagen Аноним
ACCESS MORE